The prediction of transmission loss using transfer matrix method / M. A. Yunus … [et al.] - A. Yunus, M.; Mat Isa, Ahmad Azlan; A. Rahman, Z.; Ali Al-Assadi, Hayder M. A. (UiTM Press, 2010)
Mufflers play an important role in attenuating the noise level produced by noise source especially in automotive application. A reliable, effective and affordable method in assessing and determining muffler performance in term of sound absorption criteria is therefore an important aspect to study. Different muffler configurations such as inlet and outlet pipe diameter, baffle locations, chamber length are studied with respect to the transmission loss (TL) in wide frequency range. Analytical analysis based on Transfer Matrix Method (TMM) was utilised and source code using FORTRAN was developed to accurately predict the transmission loss. The predicted numerical results with selected parameters show a very good agreement with results obtained experimentally and BEM.